Factor structure of school readiness skills: conceptual vs. statistical distinctions - Duncan, Robert J.; Anderson, Kirsten L.; Finders, Jennifer K.; Purpura, David J.; Schmitt, Sara A. (Frontiers in Psychology, 2023)
Introduction School readiness skills are a broad set of abilities that children develop in early childhood that support achievement once they enter formal schooling. Three components of school readiness skills are of focus in the current study: executive function (EF), language/literacy, and mathematics. The current study examines to what extent 13 direct assessments of these skills statistically align with theoretical models for distinct construct- and timepoint-specific latent factors. Methods The sample included 684 children (52.34% male; 42% Black/African American; Mage = 4.80 years in the fall of prekindergarten) assessed in the fall and spring of the prekindergarten year. Results Factor analyses revealed the most statistical support for a model with a latent random intercept across timepoints and constructs, along with timepoint-specific latent factors in the fall and spring of prekindergarten (independent of the random intercept). The timepoint-specific latent factors primarily consisted of early literacy and mathematics assessments. Discussion These findings challenge commonly held practices of creating construct-specific latent factors in early childhood research and, to a lesser extent, timepoint-specific latent factors without consideration of the substantial shared variance across different constructs and timepoints. Implications for the factor structure and developmental theory of school readiness skills are considered, as well as practical considerations for future research.